Nomadic pastoral tribes at the intersection of the Ottoman, Persian and Russian Empires (1820s–1890s) - Koç, Yener. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
This dissertation studies the changing military, political and economic relations between the Ottoman Empire and pastoral nomadic tribes that were wandering at the intersection of the Ottoman, Persian and Russian imperial borders during the long nineteenth century. Focusing on the nomadic pastoral Zilan, Celali and Haydaran tribes, I discuss how imperial wars, the making of the borders and imperial policies influenced tribes and tribe-state relations. It argues that despite such developments deeply influenced the political, social, and economic organization of the tribes, as well as their pastoral habitat and their local relations, these developments created new political and institutional spaces for the tribes in which they actively participated. Particular attention is paid to the frontiers of the Ottoman Empire and its tribal policy starting from the 1850s. The dissertation demonstrates how the reforms of the nineteenth century Ottoman Empire were redefined at local level in relation to the changing dynamics of tribal responses and border politics. Rather than seeing tribes and states as two hostile camps, it discusses how they complemented each other politically, militarily, and economically at several occasions. This dissertation also discusses how pasturing grounds became sites of contention among the tribes and between the peasantry and tribes during the late nineteenth century due to the increasing commercialization of the pastoral production. It indicates how direct relations between tribes and the Ottoman Empire, and the commercialization of pastoral production led to the internal stratification, and territorialization of the tribal groups.
Keywords: Nomads -- Turkey.; Nomads -- Persian.; Nomads -- Russian.; Pastoral systems.